The Antioxidant Potential of Kecombrang (Etlingera elatior) - Solihah, Indah; Syarif, Nirwan; Resmiyani, Ubbadah; Rasyid, Riana Sari Puspita; Suciati, Tri (Jurnal Penelitian Sains, 2024)
Kecombrang (Etlingera elatior) is one of the native plants of Indonesia.E.elatioris used as a condiment, food, medicine, and ornament. The antioxidant properties of rhizomes, leaves, and flowers ofE.elatiorhas not been reported. This study aimed to explore the antioxidant capacity of the rhizome, leaves, and flowers ofE.elatiorin extracts and fractions. The rhizome, leaves, and flower ofE.elatiorwere macerated by ethanol 96% to generate crude extract. The crude extract was fractionated by n-hexane, ethyl acetate, and ethanol 96% to generate n-hexane, ethyl acetate, and ethanol fraction. The total phenolic compound was determined spectrophotometrically using the follin-ciocalteau color complex. The antioxidant effect of extracts and fractions ofE.elatiorwas evaluated using DPPH scavenging activity. The largest total phenolic compound ofE.elatiorwas in the ethanolic fraction of flower (298.47mgGAE/100g), and the lowest was in a crude extract of rhizome (61.80mgGAE/100g). The very strong antioxidant capacity (IC50value <50ppm) was in crude extract, n-hexane fraction of rhizome, and an ethanolic fraction of leaves. The strong antioxidant capacity (IC50value: 50-100 ppm) was crude extract and all fractions of flower; ethyl acetate and an ethanolic fraction of rhizome; crude extract, n-hexane, and ethyl acetate fraction of leaf.The conclusion of this study is that, depending on the type of solvent, the type of antioxidant compounds being extracted and antioxidant capacity also vary.